Proposed Business Strategy Formulation for CIMB Niaga Syariah - Ghalba, Firdaus; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
Indonesia is a country that is highly developed. In the future, With a very large population, Indonesia will play a major role in the world economy,. Slowly, Indonesia becomes the world's investment objective. This makes banking industry play a major role in supporting these developments. CIMB Niaga Syariah, as part of CIMB Niaga and CIMB Group, will support the financial transactions of its customers, especially in the Islamic banking segment. Some Islamic banks in Indonesia have separated â€œspin offâ€ from the parent company to form a new legal entity. Applicable laws actually give space to Islamic banking to run business efficiently, by using office channeling scheme. CIMB Niaga calls it Dual Banking Leverage Model (DBLM). This project will define the most appropriate strategy to adopt by CIMB Niaga, by evaluating internal and external factors. The internal and external analysis are based on Islamic banking business proces, then discuss them with the management of CIMB Niaga Syariah. The writer will present early analysis in the form of questionnaires which will be distributed at several Branch Managers, Marketing/Business Managers, Support Unit at Headquarters and Dual Banking PICs. Internal and External analysis results will be established in the SWOT analysis/matrix. And then formulate strategies by using the TOWS Matrix. The outcomes of the analysis are solution and implementation, i.e forming more integrated Product Development Group, proposed partial closure of a branch which can not produce profits, and maximizing Office channeling. Supervision will also be improved with more structured program. Access to information will also be simplified for the purpose of increasing employees ability.